Hubungan Paparan Debu Kayu terhadap Gangguan Fungsi Paru pada Pekerja - Nabila Quinsy Chiqita (Jurnal Medika Hutama, 2020)
The wood processing industry has developed very rapidly, but in the processing process, the wood used produces wood dust that can be inhaled by workers and has health effects such as lung function disorders, namely the Force Expiratory Volume in 1 second (FEV1), Forced Expiratory Flow (FEF), and Forced Vital Capacity (FVC) if it has passed the Threshold Value of wood dust exposure which is 5 mg / m3. In addition to exposure to wood dust, there are other factors that can affect the occurrence of lung function disorders in these workers, which include factors of age, years of service, length of work, nutritional status, smoking history, and the use of personal protective equipment (PPE). Prevention such as routine medical observation, procurement of a good ventilation system, using wood based on particle board or medium density fibreboard, the use of personal protective equipment (PPE) such as masks, and cleaning the work environment with a vacuum can be done to avoid the risk of pulmonary function disorders and risk of other respiratory diseases that can arise from exposure to wood dust in the worker's environment